Suture manipulation post-trabeculectomy: A practical guide - Prasanna Venkataraman; Anahita Shroff (Indian Journal of Ophthalmology, 2023)
Background: Trabeculectomy is the gold standard filtration surgery for diverting aqueous from anterior chamber to the subconjunctival space. More than the surgery, postoperative follow-ups and management of the blebs play a critical role in the long-term success. This video is aimed at showing the real-world management of blebs postoperatively. Purpose: This video will serve as a practical guide to the postoperative management of trabeculectomy blebs with specific focus on the suture manipulation. Synopsis: This video will demonstrate various suturing techniques of trabeculectomy and their manipulation in the postoperative period. Complications related to each will be discussed. Highlights: We demonstrate how to place and remove, releasable, and fixed sutures. We also address the practical points on why and when to remove the sutures. Suture-related complications and their management have been shown along with practical examples. Video Link: https://youtu.be/2WFQJAPyOvY